A Comparison of Muscle Sympathetic Nerve Activity to Non-contracting Muscle During Isometric Exercise in the Upper and Lower Limbs - Boulton, Daniel; Green, Simon; Macefield, Vaughan G.; Taylor, Chloe E. (Frontiers in Neuroscience, 2019)
Previous research indicates that greater sympathetic vasoconstrictor drive to skeletal muscle occurs during isometric upper limb exercise compared to lower limb exercise. However, potential disparity between blood flow and metaboreflex activation in contracting upper and lower limbs could contribute to the augmented sympathetic response during upper limb exercise. Therefore, the aim of this study was to examine MSNA responses during ankle dorsiflexion and handgrip exercise under ischaemic conditions, in order to standardize the conditions in terms of perfusion and metaboreflex activation. Eight healthy male subjects performed 4-min contractions of ischaemic isometric handgrip and ankle dorsiflexion at ∼10% maximal voluntary contraction, followed by 6 min of post-exercise ischaemia. MSNA was recorded continuously by microneurography of the common peroneal nerve of the non-contracting leg and quantified from negative-going sympathetic spikes in the neurogram, synchronized with the cardiac cycle. The time-course of MSNA exhibited parallel increases during exercise of the upper and lower limbs, rising throughout the contraction to peak at 4 min. This represented an increase of 100% relative to resting levels for handgrip exercise (66 ± 24 vs. 33 ± 7 spikes/min at rest) and 103% for dorsiflexion (63 ± 25 vs. 31 ± 8 spikes/min at rest; P < 0.01). In both conditions MSNA remained elevated during post-exercise ischaemia and returned to pre-contraction levels during recovery. These findings demonstrate that that the MSNA response to metaboreflex activation is similar for upper and lower limb exercise when perfusion is controlled for.